Development of thermosensitive poloxamer 407-based microbubble gel with ultrasound mediation for inner ear drug delivery - Ai-Ho Liao; Cheng-Ping Shih; Ming-Wei Li; Yi-Chun Lin; Ho-Chiao Chuang; Chih-Hung Wang (Taylor & Francis Group, 2021)
Our previous study first investigated feasibility of applying ultrasound (US) and microbubbles (MBs) via external auditory canal to facilitate drug delivery into inner ear. However, most drugs are in aqueous formulae and eliminated via Eustachian tubes after drug application. In this study, feasibility of sustained release of thermosensitive poloxamer 407 (P407)-based MB gel for US mediation-enhanced inner ear drug (dexamethasone, DEX) delivery was investigated. The sol-to-gel transition temperature showed that mixture of DEX and only 10% and 12.5% P407 in MBs can be used for in vitro and in vivo drug delivery experiments. In in vitro Franz diffusion experiments, the release rates of 12.5% P407-MBs + US groups in the model using DEX as the delivered reagent at 3 h resulted in values 1.52 times greater than those of 12.5% P407-MBs groups. In guinea pigs, by filling tympanic bulla with DEX in 12.5% P407-MBs (DEX-P407-MBs), USMB applied at post-treatment days 1 and 7 induced 109.13% and 66.67% increases in DEX delivery efficiencies, respectively, compared to the group without US. On the 28th day after US-mediated P407-MB treatment, the safety assessment showed no significant changes in the hearing thresholds and no damage to the integrity of cochlea or middle ear. These are the first results to demonstrate feasibility of US-modified liquid form DEX-P407-MB cavitation for enhancing permeability of round window membrane. Then, a gel form of DEX-P407-MBs was generated and thus prolonged the release of DEX in middle ear to maintain the therapeutic DEX level in inner ear for at least 7 days.